The earth and its peoples : a global history - Bulliet, Richard W.; .; Crossley, Pamela Kyle.; Headrick, Daniel R. (Boston : Houghton Mifflin, 1997)
This book is about: The emergence of human communities; Formation of New cultural communities; Growth and interaction of cultural communities; Interregional patterns of culture and contacts; ...
Keywords: World history; World history